PATTERNS OF LANGUAGE USE AMONG MULTILINGUAL UNIVERSITY STUDENTS MAJORING IN ENGLISH - Emi Nursanti; Erna Andriyanti; Paulus Kurnianta; Titik Sudartinah (LITERA, 2020)
As a multilingual country, the Indonesian government has set the positions of local language, national language, and foreign language in education through Law of National Education System No.20 of 2003, Chapter VII, Article 33. Fifteen years passed and this paper seeks to find the results of the law in higher education students by investigating the patterns of language use of multilingual students in English Literature Study Program of FBS UNY. This is a descriptive study with parallel mixed method design. The data in this study were responses upon questions in the questionnaires distributed to respondents where the results were then analyzed quantitatively by using SPSS (17) and the results of interviews were analyzed qualitatively. The source of data in this study were 162 respondents who were students of English Literature study program, Faculty of Languages and Arts, Universitas Negeri Yogyakarta year 2015-2017. The results show that at home, more than 60% of students use Javanese with intimacy and habit as motivating factors. As English Literature students, they are more exposed to media in Bahasa Indonesia. On the campus, English is only used for academic purposes, Bahasa Indonesia for communicating with lecturers while Javanese is for a casual talk with classmates. Javanese is close to traditional commerce while for the modern one, they prefer to use Bahasa Indonesia. For cognitive and mental activities, Bahasa Indonesia is the most dominant, and Javanese is used more than English. These results imply that rather than conforming to the law made by the government, contexts play a more important role in forming people’s language choices.Keywords: multilingualism, local language, national language, foreign language, English Literature UNY POLA PENGGUNAAN BAHASA MAHASISWA MULTILINGUAL JURUSAN BAHASA INGGRISSebagai negara multibahasa, pemerintah Indonesia telah menetapkan posisi bahasa daerah, bahasa nasional, dan bahasa asing dalam pendidikan melalui Undang-Undang Sistem Pendidikan Nasional No.20 tahun 2003, Bab VII, Pasal 33. Lima belas tahun telah berlalu dan tulisan ini berupaya untuk menemukan penerapan hasil hukum tersebut pada mahasiswa dengan menyelidiki pola penggunaan bahasa mahasiswa multibahasa di Program Studi Sastra Inggris FBS UNY. Ini adalah penelitian deskriptif dengan metode campuran paralel. Data dalam penelitian ini adalah tanggapan mahasiswa terhadap pertanyaan dalam kuesioner yang hasilnya kemudian dianalisis secara kuantitatif dengan menggunakan SPSS (17) serta hasil wawancara yang dianalisis secara kualitatif. Sumber data dalam penelitian ini adalah 162 responden yang merupakan mahasiswa program studi Sastra Inggris, Fakultas Bahasa dan Seni, Universitas Negeri Yogyakarta angkatan tahun 2015-2017. Hasil penelitian ini menunjukkan bahwa di rumah, lebih dari 60% mahasiswa menggunakan bahasa Jawa dengan keakraban dan kebiasaan sebagai faktor pendorongnya. Sebagai mahasiswa Sastra Inggris, mereka lebih terpapar media dalam Bahasa Indonesia. Di kampus, bahasa Inggris hanya digunakan untuk tujuan akademik, Bahasa Indonesia untuk berkomunikasi dengan dosen, dan bahasa Jawa untuk percakapan santai dengan teman. Bahasa Jawa sangat dekat dengan perdagangan tradisional, sedangkan untuk perdagangan modern, mereka lebih memilih untuk menggunakan Bahasa Indonesia. Untuk kegiatan kognitif dan mental, Bahasa Indonesia adalah yang paling dominan, dan bahasa Jawa digunakan lebih dari bahasa Inggris. Hasil ini menyiratkan bahwa alih-alih menyesuaikan ketentuan yang telah dibuat oleh pemerintah, konteks memainkan peranan yang lebih penting dalam membentuk pilihan bahasa penggunanya.Kata kunci: multilingualisme, bahasa daerah, bahasa nasional, bahasa asing, Sastra Inggris UNY